Engaging the Authoritarian State: Voices of Protest in Syria - Athamneh, Waed; Sayej, Caroleen Marji (Journal of Arabic and Islamic Studies, 2017)
This paper captures the discursive interaction between the Syrian regime and the protesters during the revolt that began in March 2011. The purpose of this study is two-fold. First, we trace the use of symbolic rhetoric as a method of control long used by the Syrian regime to shape permissible discourses in society. The Assad family has long relied on the powerful symbols of Baathism, Pan Arabism, and resistance to colonialism to justify its rule with an iron fist. Second, we demonstrate that the protesters are using the same tactics to challenge the regime, as a form of reverse indoctrination, to undermine and counter its dominant narratives. They have engaged the authoritarian state through the use of poetry, music and slogans. The power of their words represents a symbolic collapse of the regime as the protesters negate and reinvent their political identity. Key Words: Arab Spring – Authoritarianism – Collective Resistance – Iltizām (commitment) poetry – Semiotics – Syria